Humoral immune response in rabbits experimentally infected with Trypanosoma evansi - Ghorui, S K; Srivastava, R V N; Bansal, G C; Bansal, M P (The Indian Journal of Animal Sciences, 2012)
Weekly collected sera from rabbits infected with Trypanosoma evansi were analysed for antibody by enzyme-linkedimmune assay (ELISA) to determine the dynamics of humoral immune response. The first antitrypanosomal antibodywas detected seven days post-infection and the titre gradually rose up to seventh week post-infection. Thereafter itshowed a declining tendency. The gradual increase in the serum antibody titre may be associated both way either with the production of variant antigen type (VAT) specific antibody or due to effect of invariant in the present study. Theunregulated proliferation of B-cells and eventual clonal exhaustion which was considered to be the effect of trypanosomal mitogen and increased catabolism of immunoglobulin might be involved in reduced humoral response.